توظيف متجه الانحدار الداعم لدراسة بعض العوامل المؤثرة على مرض فشل الكلوي لدى الرجال - موسى, م.م. عثمان رسول; رسول, م.م. رهیله عزیز; رسول, م.م. رهیله عزیز (Sulaimani Journal for Humanities, 2024)
The body classifies creatinine compounds as biological waste produced by the muscles, and the body gets rid of them through the kidneys, where the creatinine is transported through the bloodstream to the kidneys, the creatinine is filtered and disposed of through the urine. The data of this study were collected at the Kidney Center in Sulaimani which contains 143 cases all the cases were men. Creatinine ratio was chosen as an indicator of kidney failure, while systolic pressure, age, and protein intake were considered as explanatory variables. The support vector regression model was used in this study to estimate the effect of the three factors on the kidney creatinine level for the patients. The estimated values of the parameters of the explanatory variables are tested to verify whether they have an effect on kidney failure. The three values of the p-value column are less than the 0.01 significant levels, which means that the three factors have a statistically significant effect on the response variable. Since the systolic pressure has an effect of 0.204 on the patient, that is, if the systolic pressure increases by one unit, the creatinine percentage increases by 0.204 units. Also, both the age and the amount of protein eaten per week have a significant effect on the response variable by (0.097 and 0.310), respectively.
Keywords: Linear Regression; Support Vector Regression; kernel Functions